Research on the level of awareness and consumption of energy drinks among students aged 18-25 - Żurowska, Klaudia; Dębik, Marika; Szydłowski, Łukasz; Sajdak, Piotr; Krużel, Aleksandra; Kłos, Kamil; Stodolak, Marcel; Ziajor, Seweryn; Bednarski, Artur; Tomasik, Justyna (Journal of Education, Health and Sport, 2024)
Introduction and purpose: The article focuses on the analysis of young people's awareness of the consumption of energy drinks, especially those containing caffeine. The aim of the study is to understand the level of knowledge about the awareness and consumption of energy drinks among students aged 18-25. This study was conducted using surveys and involving 202 participants. Material and Methods: The study was conducted using online anonymous surveys, involving 202 participants. The participants were students aged 18-25 both women and men. The results were analyzed according to the age and gender. Moreover, based on the available literature examining aspects related to the consumption of energy drinks. Results: The study shows that the vast majority of respondents (94.06%) are aware of the impact of energy substances on the body. The charts also illustrate that caffeine, as the main ingredient in energy drinks, is well understood in terms of cardiovascular effects. Moreover, the student community is aware of the link between excessive sugar consumption and the risk of cancer development. Discussion: The study shows that young people are aware of the negative impact of energy drinks on health. Nevertheless, not all areas of knowledge are clear to them. The continuous increase in the level of education can undoubtedly contribute to the introduction of healthy eating habits among students. Most respondents declare to drink energy drinks again, it should draw our special attention. Conclusions: It is worth noting the need for further education, especially in the field of metabolic syndrome. It also highlights the role of research and education in shaping public health awareness. Finally, the article suggests that further research and targeted educational programs are critical to improving public health, especially in the context of energy drink consumption.